Marker-free transgenic (MFT) near-isogenic introgression lines (NIILs) of golden indica rice (cv. IR64) with accumulation of provitamin A in the endosperm tissue - Baisakh, Niranjan; Rehana, Sayda; Rai, Mayank; Oliva, Norman; Tan, Jing; Mackill, David J.; Khush, Gurdev S.; Datta, Karabi; Datta, Swapan K. (Wiley, 2006)
We have developed near‐isogenic introgression lines (NIILs) of an elite indica rice cultivar (IR64) with the genes for β‐carotene biosynthesis from dihaploid (DH) derivatives of golden japonica rice (cv. T309). A careful analysis of the DH lines indicated the integration of the genes of interest [phytoene synthase (psy) and phytoene desaturase (crtI)] and the selectable marker gene (hygromycin phosphotransferase,hph) in two unlinked loci. During subsequent crossing, progenies could be obtained carrying only the locus withpsyandcrtI, which was segregated independently from the locus containing thehphgene during meiotic segregation. The NIILs (BC2F2) showed maximum similarity with the recurrent parent cultivar IR64. Further, progenies of two NIILs were devoid of any fragments beyond the left or right border, including the chloramphenicol acetyltransferase (cat) antibiotic resistance gene of the transformation vector. Spectrophotometric readings showed the accumulation of up to 1.06 µg total carotenoids, including β‐carotene, in 1 g of the endosperm. The accumulation of β‐carotene was also evident from the clearly visible yellow colour of the polished seeds.